VASTI FOR CHD (CANINE HIP DYSPLASIA) IN ST.BERNARD DOG - A SINGLE CASE STUDY - Sankaramanchi Mrudula,; Madikonda Praveen Kumar, (International Journal of Applied Ayurved Research, 2018)
The concept of vasti as being highlighted for various virtues has a wide spectrum of practical applicability. A rational approach towards the indications of vasti holds vatarogas on a spe-cial note . There are many previously proved cases of vasti doing wonders in various sets of disorders. There are some disorders which are genetic and can be managed than being cured. Hip dysplasia is one such disorder in humans as well as quadrupeds. The animal lovers have increased in the recent past, to be precise a few decades or so where there was an increase in taming of hybrid breeds as well. Dogs are said to be the most tamed pets. St.Bernard is said to be one of the giants of the population with an average height of 70-90 cms, average weight being between 65-120kgs. The lifespan is ranging between 8-10 years.As these canines (ST.Bernards) are giants among the population and grow faster, there is a risk of having pain, discomfort in running and walking. As an attempt to reduce the dis-comfort and pain with the support of classical treatises, a minimal dose of oil and ghee with vatahara drugs was administered per rectum. This paper also discusses about the conceptual credential of prakrti assessment of dogs.The advantage of vasti in quadrupeds is that the factor of gravity doesn’t act against the vastidravya as the spine is transverse.